Salamone Rossi’s Songs of Solomon:: The Pleasures and Pains of Marginality - Patuzzi, Stefano (Music and Jewish culture in early modern Italy, 2022)
An apparent contradiction lies at the heart of Salamone Rossi’s Hashirim ’asher li-Shlomo (The Songs of Solomon) , his volume of polyphonic compositions set to Hebrew texts published in Venice in 1622-1623. The rabbinical "copyright" attached to the music states in fact that Salamone became "’adam ha-rishon le-hadpis musiqah ‘ivrit" ("the first man to print Hebrew music" or "Jewish music"; the term carries both meanings).¹ Given this claim of primacy, modern readers might expect Rossi’s musical settings to display recognizably Jewish traits beyond their Hebrew texts. However, distinctive markers of Rossi’s Jewish heritage are confined to those texts and to